RUTAS TURÍSTICAS UNA CONTRIBUCIÓN A LA COHESIÓN SOCIAL, TERRITORIAL Y EL DESARROLLO LOCAL EN ESPACIOS ANDINOS ESTUDIO DE CASO – RUTA YUYARIY DEL CÓNDOR - Eduardo Muñoz Jácome; Escuela Superior Politécnica de Chimbora (European Scientific Journal, ESJ, 2015)
Ecuador with an extraordinary variety of life zones is a tourist power. Chimborazo province in the Ecuadorian Andes with natural and cultural wealth, through their national government authorities introduced in 2014 a proposal for changing the productive matrix including tourism. San Juan is a rural parish, here is the watershed of the Rio Chimborazo, indigenous population in 93%; part of the faunal reserve production of the same name, one of the best preserved and visited the country, owns the highest mountain Ecuador, Chimborazo, with 6310 meters. Chimborazo has a wonderful landscape that enjoys with other attractions of neighboring provinces from the trip on the world's highest railway, however the watershed despite having cultural and natural attractions of tourist hierarchy has not been exploited for lack integration of these products recognized nationally and globally, either for tourism have been utilized by the nearest local people, the inhabitants of the city of Riobamba. The commercial path analysis using empirical research methods, applying descriptive and inferential statistical techniques, helped to show that this tourism concept, considering its acceptance, tastes and preferences of potential visitors and closest contributes to integration urban - rural, social and territorial cohesion, contributes to local sustainable development, good living and changing the productive matrix giving added value to the high Andean territories.